(3YdGbI GdGYdGe GdOhdj HGdbGfhf GdOhdj GdYGe h JCKjQg aj bQGQGJ GdefXeGJ GdOhdjI (B/s - (3OQHGT, eaJGM YeQs ((3YeGf (B:s (3OGQ RgQGf ddfTQ h GdJhRjY ,s, 2014)
(3GdaUd GdGhd jJVef eaghe GdGYdGe GdOhdj h JWhQg GdbGfhf GdOhdj h Gdabg GdGSdGej GeG GdaUd GdKGfj jJMOK Yf fTGI h JWhQ hSGFd GdGYdGe GdOhdj h GdaUd GdKGdK NUU defGbTI ehVhY GdGYdGee GdOhdj aj Xd GdYhdeI h GdgjefI GdZQHjI GeG GdaUd GdQGHY aGfg jQcR Ydi bQGQGJ GdefXeGJ GdOhdjI h GNjQG GdaUd GdNGeS jYGdL SdWI GUOGQ GdbQGQGJ aj GdefXeGJ GdOhdj h eOi JGKQgG HGdGYdGe GdOhdj Je fNJe GdcJGH HNGJeI fJfGhd ajgG Gge fJGFL GdJj Je GdJhUd GdjgG h GdJhUjGJs
(3HHdjhZQGajG (B: (3U(B.197-203s
Keywords: (3GdEYdGe GdOhdjs; (3GdbGfhf GdOhdjs; (3GdEYdGes